Comparison of panoramic radiography and lateral cephalomerty in measurement of gonial angle in patients with Class II malocclusion - j Chalipa; V Rezayani; A Khorshidian; Mh Hosseini; MS Ahmad Akhoundi (Isfahan University of Medical Sciences, 2009)
Introduction: Orthodontic diagnosis and treatment plans always require radiographic investigation. The investigation mostly used is lateral cephalometry. Reliable measurement of individual gonial angle is very difficult, because of the superimposed images appearing on the lateral cephalogerams. This disadvantage is not encountered in panoramic radiography. The aim of this study was to evaluate the potential of panoramic radiograph to accurately measure gonial angle.Materials & Methods: In this cross- sectional study, standard panoramic and lateral cephalometry radiographs were taken for 281 patients by mean age of 9-10 years. Gonial angle from panoramic and lateral cephalometry radiographs was measured. The measurements were analyzed by paired student t- test.Results: Paired t- test was performed to check for similarity between the measurements. No significant differences were found between the gonial angle when comparing panoramic and lateral cephalometry radiographs (p value > 0.05); also no significant differences between right and left gonial angle of individuals were found (p value > 0.05).Conclusion: Measurement of gonial angle in right and left sections of panoramic radiograph didn't show any differences statistically. That was also the case in panoramic in comparison with lateral cephalometric radiograph. Panoramic radiograph is a useful tool for the measurement of gonial angle, which is an indicator of mandibular growth direction.Key words: Radiography, Panoramic, Cephalometry, Gonial angle, Malocclusion, Angle